PENGARUH PENAMBAHAN BUBUR BUAH TOMAT TERHADAP KUALITAS DODOL TOMAT - Noviana, Kiki; Wijaya, Mohammad; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
Dodol was a  processed product of agricultural  that are semi-wet, white to brown, made of a mixture of glutinous rice flour, coconut milk, sugar with or without preservatives. The aims of this research was to determine the quality and nutritional value of the tomato dodol. This research was used a completely randomized design (CRD). The data of this research were quantitative data. The quantitative data obtained from analysis of variation (ANOVA) and foellowed by DMRT examine. Based on the research,  the quality of tomatoes dodol that was  produced show that the addicting of tomatoes puree was gave significant effect on moisture content, fat and carbohydrate levels in tomato dodol. Treatment  Of addicting of tomato fruit puree  with 25%  of tomato fruit puree is the best treatment to produce nutritional value, 16.92 of moisture content. 7.96 of fat content. and 39.91 of carbohydrate content